2012
DOI: 10.1007/s00264-012-1722-3
|View full text |Cite
|
Sign up to set email alerts
|

Pain and function in eight hundred and fifty nine patients comparing shoulder hemiprostheses, resurfacing prostheses, reversed total and conventional total prostheses

Abstract: Purpose Functional results of reversed total prostheses (RTP) have-to a very limited degree-been compared with those of other shoulder prosthesis types. The aim of our study was to compare results of four different types of shoulder prostheses in terms of function, pain, and quality of life (QoL). Methods Questionnaires were completed by 859 patients with shoulder prostheses registered in the Norwegian Arthroplasty Register. Patients with osteoarthritis (OA), rheumatoid arthritis (RA), or fracture sequela (FS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 29 publications
(23 reference statements)
2
21
0
1
Order By: Relevance
“…In osteoarthritis patients, there was a higher risk with hemiprostheses than with total prostheses. This result is in accordance with other studies indicating a superior outcome with a total prosthesis compared to a hemiprosthesis ( Bryant et al 2005 , Radnay et al 2007 , Singh et al 2010 , Fevang et al 2013 ). As in all registry studies, a limitation exists in the completeness and reliability of registry data such as prosthesis type and supplementary surgery, and this problem is not easy to quantify.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In osteoarthritis patients, there was a higher risk with hemiprostheses than with total prostheses. This result is in accordance with other studies indicating a superior outcome with a total prosthesis compared to a hemiprosthesis ( Bryant et al 2005 , Radnay et al 2007 , Singh et al 2010 , Fevang et al 2013 ). As in all registry studies, a limitation exists in the completeness and reliability of registry data such as prosthesis type and supplementary surgery, and this problem is not easy to quantify.…”
Section: Discussionsupporting
confidence: 93%
“…Trials of shoulder replacement surgery have more commonly reported pain relief, or a composite score including pain, rather than the prevalence of pain at follow-up. There has been very little research on predictive factors for persistent postsurgical pain following shoulder replacement, but the general outcome has been shown to be associated with diagnosis and prosthesis type ( Radnay et al 2007 , Fevang et al 2013 ) and with previous shoulder surgery, age, and preoperative Short Form-36 mental score and DASH functional score ( Simmen et al 2008 ). Identification of subgroups at increased risk is important in order to establish interventions to prevent or minimize the impact of persistent postsurgical pain.…”
mentioning
confidence: 99%
“…This finding contrasts that of our previous article evaluating shoulder prosthesis survival, where failure rates of total prostheses were found to be high ( Fevang et al 2009 ). Cochrane reviews ( Bryant et al 2005 , Singh et al 2010 ) and reports from our own studies ( Fevang et al 2012 , Fevang et al 2013 ) showing superior functional results with ATPs may have contributed to the increasing use of such prostheses in Norway. This has most likely resulted in improvements in surgical experience and skills with these prostheses, ultimately leading to improved implant survival.…”
Section: Discussionmentioning
confidence: 91%
“…In a previous study from the Norwegian Arthroplasty Register (NAR), we reported superior results in terms of prosthesis survival with shoulder hemiprostheses (HPs) than with total prostheses (TPs), both anatomic and reverse ( Fevang et al 2009 ). However, several other studies have shown better functional results with the use of TPs than with HPs ( Bryant et al 2005 , Pfahler et al 2006 , Radnay et al 2007 ), and in a recent report from the NAR in which functional outcome was evaluated, patients with HPs came out worst for all variables measured ( Fevang et al 2013 ). Based on these studies and treatment practice in other countries, a change in treatment policy has taken place in Norway—towards reduced use of HPs and increasing use of TPs, both anatomic and reversed types.…”
mentioning
confidence: 93%
“…Spalle rigide con deformità dell'omero prossimale, danni ai tessuti molli, esiti cicatriziali e lesioni della cuffia dei rotatori possono rendere la protesizzazione dell'articolazione glenoomerale una procedura molto complessa, spesso con risultati imprevedibili e con un più alto rischio di complicanze. I risultati medi ottenuti nei pazienti in esiti traumatici sono inferiori rispetto a quelli ottenuti nel trattamento delle fratture in acuto o dell'artrosi primaria [5,[20][21][22]. Il trattamento delle sequele traumatiche con una protesi anatomica porta a un netto miglioramento della sintomatologia dolorosa.…”
Section: Discussioneunclassified